Confirmation of a crisis leadership model and its effectiveness: Lessons from the COVID-19 pandemic - Balasubramanian, Sreejith; Fernandes, Cedwyn (Cogent business & management, 2022)
Despite the significance of crisis leadership for organizations, especially in the wake of COVID-19, empirical research in this area is still nascent. Therefore, "What attributes make an effective leader during a crisis?" is unclear. Using lessons learned from the COVID-19 pandemic, this study seeks to address this gap in the literature by i) developing and validating a robust multi-dimensional crisis leadership model and ii) measure its effectiveness in handling the crisis. A higher-order measurement model of crisis leadership comprising of seven constructs (compassion and care, openness and communication, resilience and courage, decisiveness, consultation and collaboration, and empowerment) and two structural models to measure its predictive validity (effectiveness in handling the crisis) were proposed based on the review of crisis leadership literature. Next, using data collected through a global survey, the validity of the proposed models, including the relevance/appropriateness of each construct and the predictive power of the crisis leadership model in explaining the organizations' effectiveness in handling the crisis, were assessed. The second-order confirmatory factor analysis established the existence of a higher-order measurement model for crisis leadership, with each of the seven constructs contributing uniquely and strongly. The structural equation modeling results confirmed the strong predictive power of the crisis leadership model in explaining the organizations' effectiveness in handling the crisis across its different (beginning, current, and future) phases. The findings show that crisis leadership is multifaceted and requires an all-encompassing effort and provides a road map for organizations looking to develop crisis leadership capabilities for senior managers and leaders.